FAKTOR-FAKTOR YANG MEMPENGARUHI KELENGKAPAN PENGUNGKAPAN LAPORAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013 – 2015 - Nesya Sefi Ayundari, 12.05.52.0102; Aini, Nur (Students' Journal of Accounting and Banking, 2018)
This study aims to determine the Factors Affecting Financial Statement Disclosure Completeness in Manufacturing Companies Listed on Indonesia Stock Exchange Period 2013 - 2015. The population in this study is a manufacturing company listed on the stock exchange Indonesia in 2013-2015. The sample in this research is taken with Purposive Sampling method. Data were analyzed by using Independent sample t test.In the variable leverage statistically significant positive effect on the completeness of financial reporting disclosure, In the liquidity variable statistically significant positive effect on the completeness of financial reporting disclosure, On variable profitability statistically significant effect on the completeness of financial report disclosure, In the variable age of the company statistically positive significant to the completeness of financial reporting disclosure, On variable size of company statistically significant positive effect on the completeness of financial reporting disclosure.Keywords: leverage, liquidity, profitability, company age, firm size, completeness of financial reporting disclosur